PENGARUH PEMBELAJARAN BLENDED LEARNING TERHADAP KEMANDIRIAN BELAJAR SISWA KELAS X SMK NEGERI 2 BONE - Selpi; Suhardiman; Ahmad Nurul Ihsan B (Lembaga Berugak Baca, 2024)
This research aims to determine the influence of Blended Learning on student self-directed learning in Grade X of SMK Negeri 2 Bone. The research was conducted from July to August 2023. This study is a quantitative descriptive research. The research population consisted of 304 students in Grade X of DKV at SMK Negeri 2 Bone, with a sample of 55 students. Data collection in the research process was carried out using questionnaires and documentation. Based on the research results, it is found that the respondents' perceptions of Blended Learning in relation to student self-directed learning amounted to 75%. This indicates that the respondents' opinions fall within the